Geographic Analysis of Extractive Industries in Wasit Province - Esraa Abdulmonem Saleh Waheeb; Asst. Prof. Dr. Mohammed Abbas Majeed (Journal of College of Education, 2025)
The research addressed Extractive Industries in Wasit Governorate, which rely on natural resources and minerals that are economically depletable. These resources are distributed unevenly across the administrative units in the governorate according to their geographical location. Among the most important are the oil industries, as this activity aims to extract crude oil from underground and exploit it for export purposes or internal and external marketing. In addition to quarries and factories, which are considered the natural repository for minerals, rocks and quarry resources such as sand, gravel and gypsum, this research came to shed light on different mining methods. Furthermore, it highlights the economic importance of deposits, especially after the year 2000, with urban development and city expansion. These deposits are characterised by their proximity to the earth’s surface, with the distance of these deposits from their sources not exceeding 20 km due to their high density. The method of transporting extracted materials generally depends on the type and size of the mining industry. Some are transported by pipelines and tankers, such as oil and gas industries, while others are transported in stages, such as quarries, which rely on various heavy machinery in the transportation process before being loaded onto cargo vehicles. We can say that any region grows and develops through its possession of industrial activity capable of providing and meeting the requirements of the population, raising their living standards and developing them socially, economically and architecturally by providing job opportunities, solving the problem of unemployment and increasing per capita income, which directly reflects on the economic situation in Wasit Governorate